Recent advances in de-intensification of radiotherapy in elderly cancer patients [version 1; peer review: 2 approved] - Isacco Desideri; Viola Salvestrini; Lorenzo Livi (F1000Research, 2020)
Cancer in the elderly remains an evolving issue and a health challenge. Several improvements in the radiotherapy field allow the delivery of higher doses/fractions with a safe toxicity profile, permitting the reduction of radiation treatment protocols in the elderly. Regarding breast, prostate, and lung cancer, the under-representation of older patients in clinical trials limits the extension of treatment recommendations to elderly patients in routine clinical practice. Among the feasible alternatives to standard whole breast radiotherapy (WBRT) in older patients are shorter courses using higher hypofractionation (HF) and accelerated partial breast irradiation (APBI). The boost continues to be used in women at high risk of local recurrence but is less widely accepted for women at lower risk and patients over 70 years of age. Regarding prostate cancer, there are no published studies with a focus on the elderly. Current management decisions are based on life expectancy and geriatric assessment. Regimens of HF and ultra-HF protocols are feasible strategies for older patients. Several prospective non-randomized studies have documented the safe delivery of ultra-HF for patients with localized prostate cancer, and multiple phase III trials and meta-analyses have confirmed that the HF regimen should be offered with similar acute toxicity regardless of patient age and comorbidity. A recent pooled analysis from two randomized trials comparing surgery to stereotactic body radiation therapy (SBRT) in older adult patients with early stage non-small cell lung cancer did show comparable outcomes between surgery and SBRT. Elderly cancer patients are significantly under-represented in all clinical trials. Thus, the inclusion of older patients in clinical studies should be strongly encouraged to strengthen the evidence base for this age group. We suggest that the creation of oncogeriatric coordination units may promote individualized care protocols, avoid overtreatment with aggressive and unrecommended therapies, and support de-escalating treatment in elderly cancer patients.